KLASIFIKASI TANAH GAMBUT TOPOGEN YANG DIJADIKAN SAWAH DAN DIALIHFUNGSIKAN MENJADI PERTANAMAN KOPI ARABIKA DAN HORTIKULTURA - Linda Wati Sihite; Posma Marbun; Mukhlis Mukhlis (Jurnal Agroekoteknologi, 2013)
ABSTRACTThis research is aimed to know the changes classification of topogenous peat soil that increased intopaddy field and be converted into arabica coffee (Coffea arabica) and horticulture farm begin fromOrder class, Sub Order, Great Group unto Sub Group class. This research was conducted in DesaHutabagasan, Kecamatan Doloksanggul, Kabupaten Humbang Hasundutan and soil analyseproperties was held in Chemical and Soil fertility Laboratory, Agriculture Faculty of NorthSumatera University. Observation and description of three profiles of each three difference landuses such as paddy field (P1), arabica coffe farm (P2) and horticulture farm (P3). Each profile isobserved about morphology and than classificatied in Soil Taxonomy (2010) begin from Orderclass, Sub Order, Great Group unto Sub Group class. From research result indicate that the landconversion didn’t change soil classification in Desa Hutabagasan, Kecamatan Doloksanggul,Kabupaten Humbang Hasundutan. The Topogenous peat soil in this area have soil classificationTypic Haplosaprist.Keywords: peat soil, land conversion, paddy soil